Analysis of Readiness for Merdeka Curriculum Implementation: Case Study at SD/MI Lombok Tengah - Hikmah Ramdhani Putri; Arif Widodo; Fitri Puji Astria; Umar; Hasnawati (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2023)
Merdeka Curriculum has been implemented nationally starting in the academic year 2021/2022 in the schools that participated in the program. Gradually, in the following years, each educational unit can choose to implement Merdeka Curriculum based on their respective readiness. The government has prepared standard levels of readiness to implement Merdeka Curriculum, which consists of four levels. The first level is called the initial stage, the second level is the developing stage, the third level is called the ready stage, and the fourth level is the advanced stage. This research aims to determine the level of readiness of SD/MI in implementing the Merdeka curriculum. The research uses a qualitative research method with a case study approach. Data collection uses observation, questionnaires, and interviews. The research subjects were 18 SD/MI in Lombok Tengah regency. The sources of information were school principals and teachers. The research results show that most of SD/MI are still at the second level of readiness, namely at the developing level. Few schools are only at the ready and advanced stage levels. Based on the research results, it is recommended that policymakers are able to evaluate so that the level of school readiness in implementing the Merdeka Curriculum can increase.